DOCKING ANTIOXIDANT ACTIVITY ON HYDROXY (DIPHENYL) ACETICACID AND ITS DERIVATIVES - Rajendran, Sudha; G, Nithya; P, Brindha Devi; Kanakam, Charles C (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The antioxidant activity of the synthesized compounds along with the standard compound for comparison is reported. There is comparison of binding analysis and the ligand interaction of the compound. Methods: The protein crystal structure complexed with 4-methyl-6-[2-(5-morpholin-4-ylpyridin-3-yl)ethyl]pyridin-2-amine inhibitor was selected from Protein Data Bank (5FVP) for our study. Results: The docking studies and structure-activity relationship reveals that the compound 2'-chloro-4-methoxy-3nitro benzilic acid after three different docking strategies reveals that the score was found to be higher compared with others. Conclusion: Based on the in vitro antioxidant results, the compounds synthesized were investigated for the molecular docking study to identify the amino acid interactions in the active site pocket of nitric oxide synthase enzyme. Based on the docking score results, all the compounds were oriented toward the active site pocket occupied by the cocrystallized ligand